The Role of Oxidative Stress and Natural Antioxidants in Ovarian Aging - Yang, Liuqing; Chen, Yun; Liu, Yan; Xing, Yu; Miao, Chenyun; Zhao, Ying; Chang, Xiangwei; Zhang, Qin (Frontiers in Pharmacology, 2021)
The ovarian system is comprised of vital organs in females as they are of great significance for maintaining reproductive potential and endocrine stability. Female ovarian aging occurs far earlier than the aging of other organs, and is a pacemaker of female body aging. This drives the aging of multiple organs and leads to several aging-related disorders. Although complex pathogenesis undoubtedly contributes to ovarian aging, increasing attention has been paid to the extensive influence of oxidative stress. Recently, a new study published in Cell by Izpisua Belmonte et al. showed that oxidative stress is a crucial factor in ovarian functional decline with age. Exploring oxidative stress-related processes might be a winning strategy against ovarian aging. The role of natural antioxidants in anti‐ovarian aging is gaining increasing attention owing to their excellent antioxidant capacity, high safety, and rich sources. In this review, new insights into oxidative stress-driven pathologies in ovarian aging will be provided, and the previously reported natural antioxidants involved in the inhibition of ovarian aging progression will be summarized. These facts will be enlightening for future intervention in ovarian aging and its related diseases.